2016
DOI: 10.1080/09168451.2015.1132148
|View full text |Cite
|
Sign up to set email alerts
|

Activation of transient receptor potential ankyrin 1 by quercetin and its analogs

Abstract: The agonistic activity of quercetin and its analogs towards the transient receptor potential ankyrin 1 (TRPA1) has been experimentally investigated. The human TRPA1 was expressed in HEK293T cells using a tetracycline-inducible system. The activation of TRPA1 was evaluated by a fluo-4 fluorescence assay based on calcium sensing. The results of a structure-activity relationship study led to the selection of six flavonoids, all of which activated the TRPA1 channel in a dose-dependent manner. Notably, the activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Moringa leaves have also been reported to contain various types of flavonol glycosides, as well as kaempferol, rutin, and quercetin [54]. Additionally, these flavonols are TRPA1 agonists [55].…”
Section: Discussionmentioning
confidence: 99%
“…Moringa leaves have also been reported to contain various types of flavonol glycosides, as well as kaempferol, rutin, and quercetin [54]. Additionally, these flavonols are TRPA1 agonists [55].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Nakamura T et al . found that methylated quercetin may bind with the transient receptor potential ankyrin 1 (TRPA1) and acts as agonist for this molecule, which may be the receptor for quercetin 48 . Quercetin exerts suppressive effects on the expression of collagen in lung fibroblasts by regulating the translocation of the nuclear factor E2-related factor-2 (Nrf2), an important transcription factor that regulates the expression of HO-1 from the cytoplasm to the nuclei 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Several phytochemicals that interact with TRP channels were shown to be potential treatments for COVID-19 [ [121] , [122] , [123] , [124] , [125] , [126] , [127] , [128] , [129] , [130] , [131] , [132] , [133] , [134] , [135] , [136] , [137] , [138] , [139] , [140] , [141] , [142] ]. However, the implication of TRP channel in their mechanism of action had not been investigated yet.…”
Section: Resultsmentioning
confidence: 99%
“…Quercetin is a well known a ligand for TRPM7, TRPV1 and TRPA1 channels [ [133] , [134] , [135] ]. In a prospective, randomized, controlled, and open-label study, a daily dose of 1000 mg of quercetin was given for 30 days to 152 COVID-19 outpatients to study its adjuvant effect in treating the early symptoms and in preventing the severe consequences of the disease.…”
Section: Resultsmentioning
confidence: 99%